MATURITY, SPAWNING AND FECUNDITY OF CATFISH TACHYSURUS TENUlSPINIS (DAY) - Dan, S S (Indian Journal of Fisheries, 2011)
Catfishes form an important fishery along the north-ea,st coast of India contributing 20.8% of Ithe demersal-fish crutches (Sekhalran et al. 1973) and about 4% of ,the annuaJ fish landings of the Andhra coast (Anon 1972). Tachysurus tenuispinisal10ne forms 60.7% of the Itotal catfish catches along the Andhra Coast.